Current Issues of Management under the Conditions of Innovative Development of Economy (Ternopil, TNEU, 17 April 2019) - Shkilniak and other, Mykhailo (Herald of Economics, 2019)
Analytical note on the results All-Ukrainian scientific-practical conferencewith international participation "Actual problems of management in the context of innovative economic development» (Ternopil, TNEU, April 17, 2019)